2015
DOI: 10.1103/physrevb.91.184108
|View full text |Cite
|
Sign up to set email alerts
|

Lattice-based Monte Carlo simulations of the electrocaloric effect in ferroelectrics and relaxor ferroelectrics

Abstract: Canonical and microcanonical Monte Carlo simulations are carried out to study the electrocaloric effect (ECE) in ferroelectrics and relaxor ferroelectrics (RFEs) by direct computation of field-induced temperature variations at the ferroelectric-to-paraelectric phase transition and the nonergodic-to-ergodic state transformation. A lattice-based Hamiltonian is introduced, which includes a thermal energy, a Landau-type term, a dipole-dipole interaction energy, a gradient term representing the domain-wall energy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…In addition, deeper insights into the contributions of ferroelectric switching, 105,106 domain growth, 107,108 and domain wall [109][110][111][112] to the electrocaloric effect are highly desired in order to provide basic understandings. For instance, a recent study using non-adiabatic direct measurement on PZT-5 ceramics showed that DT displays a hysteresis behavior with E and the sign of electrocaloric effect reverses at the coercive field where polarization switching occurs.…”
Section: F Heat Capacity and Kineticsmentioning
confidence: 99%
“…In addition, deeper insights into the contributions of ferroelectric switching, 105,106 domain growth, 107,108 and domain wall [109][110][111][112] to the electrocaloric effect are highly desired in order to provide basic understandings. For instance, a recent study using non-adiabatic direct measurement on PZT-5 ceramics showed that DT displays a hysteresis behavior with E and the sign of electrocaloric effect reverses at the coercive field where polarization switching occurs.…”
Section: F Heat Capacity and Kineticsmentioning
confidence: 99%
“…The adiabatic condition can be strictly fulfilled in MonteCarlo and Molecular Dynamics simulations by utilizing the direct method. 6,[10][11][12][13][14] In these methods, the information of the entropy change can be hardly extracted, which is, however, very important for the understanding of the maximal EC cooling point. In this study, we propose a direct method to analyze the entropy changes in an irreversible process, and apply it to reveal the optimal reversed electric field which maximizes the EC cooling.…”
Section: -3mentioning
confidence: 99%
“…We apply a lattice-based microcanonical Monte Carlo scheme to directly calculate the electrocaloric effect (ECE) [17]. This Hamiltonian consists of the potential energy and the thermal energy .…”
Section: Modelmentioning
confidence: 99%
“…We modified a widely accepted model [11]- [16] to evaluate the ECE in relaxor ferroelectrics in the previous work [17]. In that work, the random fields are introduced to reproduce the relaxor behavior, and are randomly distributed between 0 ∘ and 360 ∘ , and the magnitude is between 0 and an allowed maximum value | |.…”
Section: Introductionmentioning
confidence: 99%